PENERAPAN STRATEGI PEMBELAJARAN CONTEXTAL TEACHING AND LEARNING DALAM PENDIDIKAN AGAMA ISLAM DI SMK NEGERI 2 TUREN KABUPATEN MALANG - Atisatul Mukaromah; Ahmad Subekti; Ibnu Jazari (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
Contextual Teaching and Learning Learning Strategy is a learning strategy thatt emphasizes students to be involved directly and actively that is able to connect the knowledge possessed with material in the learning process and can apply it in everyday life. The process of Islamic religious education tends to use lecture and question and answer methods so that it does not make students active in the learning process and lacks understanding of the material and less motivates students in learning Islamic religious education. For that contextual teaching and learning learning strategies really help develop learning motivation etc. student learning outcomes. Researchers carry out research related to the application of contextual teaching and learning learning strategies in Islamic Religious Education. The focus of the research relates to the application of strategy, supporting and inhibiting factors for implementing the strategy, and the impact of implementing the strategy. Researchers used a qualitative approach to the type of descriptive qualitative research. Data collection techniques using observation, interviews, and documentation. In its application the teacher performs according to contextual teaching and learning by involving seven main components of effective learning, namely: constructivism, asking questions, finding (inquiry), learning communities (learning comunity), modeling (modeling), reflection (reflection), and research actually (authentic assessment). Kata Kunci: Strategi Pembelajaran, Pembelajaran Contextual Teaching and Learning, Pendidikan Agama Islam